COVID-19 Immunity in the Cohort of IRCCS San Raffaele Hospital Employees after BNT162b2 Vaccination: A Retrospective Observational Study - Stocchi, Manuel; Melodia, Pietro; Lucini, Alessandro; De Lorenzo, Rebecca; Pozzi, Carola; Rovere-Querini, Patrizia; Odone, Anna; Renzi, Cristina; Signorelli, Carlo (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The COVID-19 pandemic represents the most severe health and socioeconomic crisis of our century. It began with the first reports in China, in the Wuhan region in December 2019, and quickly spread worldwide, causing a new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Among the population most at risk of infection and developing severe forms of the disease are the elderly and healthcare workers, who are more exposed to infected individuals. On December 11, 2020, the Food and Drug Administration approved the emergency use of the BNT162b2 vaccine, the first mRNA vaccine in history. Since then, the total number of vaccine doses administered has exceeded 12 billion. Italy was the first European country to be affected by the pandemic, recording the highest number of total COVID-19 cases (25,695,311) and, after the first 70 days, had the highest crude mortality rate (141.0 per 100,000). In this study, we analyze the rate of SARS-CoV-2 infection among healthcare workers at the San Raffaele Scientific Institute in Milan before and after receiving the BNT162b2 vaccine. Study design. Retrospective observational cohort study. Methods. The study analyzed the immunization status of 858 employees of the San Raffaele Scientific Institute in Milan, including doctors, healthcare workers, and administrative staff. The analysis is based on previous studies on the same cohort and is integrated with extrapolation and additional analysis of data from the Preventive Medicine Service’s Biobank dataset of the same hospital to estimate the infection rate, duration of the disease, and antibody levels recorded in the personnel before and after receiving the double BNT162b2 vaccination. Results. The analysis confirms the positive impact achieved by the introduction of mRNA vaccination in reducing the SARS-CoV-2 infection rate and increasing antibody levels in healthcare workers. Although the BNT162b2 vaccination may not provide complete protection against SARS-CoV-2, it appears to be able to reduce the number of infections, particularly the more severe and symptomatic forms often detected in individuals with various risk factors and comorbidities, making them more vulnerable. Healthcare workers, who have extensive contact with patients and record the greatest decrease in the infection rates, represent the population that receives the most benefit from vaccination. Conclusions. The evidence suggests that vaccinations are essential in protecting high-risk groups, such as healthcare workers, from SARS-CoV-2 infection. Providing adequate vaccination coverage to healthcare workers limits the spread of infections and decreases the severity of disease manifestations, while also reducing their duration.